Bucu Kendit - Fitri, Nur Lailatul; Fatimah, Siti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Local traditions serve as essential sources of values and wisdom that strengthen character education while preserving the nation’s cultural identity. One tradition rich in philosophical meaning is Bucu Kendit, practiced by the Montong community in Tuban, East Java, which is now increasingly marginalized due to globalization. This study aims to reveal the philosophical meanings and character education values embedded in the Bucu Kendit tradition, as well as its contribution to strengthening cultural identity and youth character formation. The research method employed a qualitative approach with an ethnographic design through in-depth interviews, participant observation, and literature review. The findings show that the Bucu Kendit tradition embodies values of religiosity, social solidarity, integrity, discipline, and respect for nature values aligned with the dimensions of character education in the global era. Revitalization efforts include integrating traditional values into school curricula, developing culture-based extracurricular activities, and utilizing digital media to broaden the reach of cultural education. The implication is that the Bucu Kendit tradition plays a strategic role in reinforcing local cultural identity while nurturing a generation rooted in local wisdom yet adaptable to global change